Egg Production and Distribution - Fitriani Fitriani; Hanung Ismono; Novi Rosanti (Politeknik Negeri Lampung, 2012)
The average of egg consumption in Lampung reaches 20% through food household expenditure. It means that egg as important food to supplement protein needs must be accessible to the community. This research aimed (1) to investigate the egg production system; and (2) to investigate the distribution chain and marketing efficiency of egg from production center to consumers in Lampung Province. The research samples were taken by purposive and snowball sampling, involving egg producers and traders in any level. Egg production centers in Jati Mulyo District, South Lampung Regency, and trading centers in Bandar Lampung were chosen as research locations. Descriptive analysis was applied in investigating the egg production system dan distribution chain. The methods used to evaluate the efficiency of marketing system were Ratio Profit Margin (RPM) and Price Transmission Elasticity methods. The research results showed that on average, the egg production still faced high cost production because of high feeding cost. The egg distribution margin tended to show inefficient condition because the traders in any level got different benefit from that of producers. The value of Price Transmission Elasticity was lower than one. This condition means that the marketing system of egg is inefficient. The egg marketing tends to be imperfect competition or there is oligopsony or monopsony practice. Keywords: egg production, egg distribution chain, marketing system.